2011
DOI: 10.1089/neu.2011.1832
|View full text |Cite
|
Sign up to set email alerts
|

Novel Model to Investigate Blast Injury in the Central Nervous System

Abstract: Blast-induced neurotrauma (BINT) is a common injury modality associated with the current war efforts and increasing levels of terrorist activity. Exposure to the primary blast wave generated by explosive devices causes significant neurological deficits and is responsible for many of the war-related pathologies. Despite research efforts, the mechanism of injury is still poorly understood. To this end, we have established a novel ex vivo model for the direct observation and quantification of BINT at the tissue l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…Previously published in vitro models of bTBI have reported the incident overpressure of the blast wave but not the loading conditions at the tissue-level (Leung et al, 2008; Arun et al, 2011; Connell et al, 2011). Without a tissue-level biomechanical context, it is difficult to make quantitative comparisons between biological outcomes from different studies given the potential for vastly different loading conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published in vitro models of bTBI have reported the incident overpressure of the blast wave but not the loading conditions at the tissue-level (Leung et al, 2008; Arun et al, 2011; Connell et al, 2011). Without a tissue-level biomechanical context, it is difficult to make quantitative comparisons between biological outcomes from different studies given the potential for vastly different loading conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The injury biomechanics at the sample-level were not reported. In a different in vitro blast injury model, the excised spinal cord was subjected to strains as high as 60% with a jet of gas produced by a blast tube, which did not accurately reproduce the low strain, high strain rate biomechanics of blast (Connell et al, 2011). In each of these previous studies, overpressures were applied directly to the culture preparations, so the loading conditions were not representative of internal physiological loading conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Their methodology consisted of exposing a 96 well plate of cell cultures sealed with a gas permeable membrane to air-driven shock tube blasts of 94, 125, and 145 kPa peak incident overpressure (overpressure duration not provided), although actual pressures exposed to the cell cultures inside the blasted plate were not reported. Connell et al (2011) developed an in vitro model of the isolated guinea pig spinal cord exposed to blast overpressures and found a reduction in the conduction of action potentials and a decrease in membrane integrity (Connell et al, 2011). Their test methodology consisted of exposing an isolated spinal cord directly to a jet of gas produced by a blast tube with overpressure levels of 23, 41, and 65 kPa peak incident pressure (0.2 ms duration for all blasts).…”
Section: Discussionmentioning
confidence: 99%
“…However, results from experimental studies using animal models of blast exposure have demonstrated that direct blast shockwave is capable of penetrating the calvarium [Chavko et al, 2007] and can induce high strain rates leading to structural deficits such as axonal membrane disruption [Connell et al, 2011], myelin disruption, and neuronal death [Cernak et al, 2001;Saljo et al, 2002], as well as altered brain function .…”
Section: Introductionmentioning
confidence: 99%